Relationship Between Dental Caries Levels and Quality of Life Among Students at the Faculty of Education, Mulawarman University - Edi Wibowo; Endang Sawitri; Dame Rimmauli S; Dewi Arsih S; Listyawati (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: : Teeth and mouth are parts of the body as a whole that have a function to support and enable humans to function essentially. The mouth is also a fundamental feature in a person's identity. The existence of diseases of the teeth and mouth such as caries can cause disruption of oral health conditions and reduce a person's quality of life. Therefore, this research was conducted to find out the relationship between the level of dental caries experienced and the quality of life of students at the Teaching Faculty of Mulawarman University. Material and Methods: This research is an analytical observational study with a cross-sectional study design. This research involved 96 students from the 2018-2021 class who were selected using a stratified random sampling technique. This study used the OHIP-14 questionnaire to measure quality of life and oral photographs to measure the level of caries. Research data was analyzed using the Spearman test. Results and Discussions: The research results showed that the level of dental caries among Mulawarman University students was 2.43 in the low category and the majority of students' quality of life level was good at 54%. The results of the relationship analysis show p = 0.000 (p < 0.05); rho = 0.703. Conclusion: There is a relationship between the level of caries and the quality of life in students at the Teaching Faculty at Mulawarman University with strong strength and a positive direction of the relationship.